Periprosthetic Fractures About the Hip: A Case-Matched Retrospective Analysis of Functional Outcomes Postrehabilitation. (September 2015) - Cassidy, J. Tristan; Baker, Joseph F.; Keogh, Peter; Kenny, Paddy
Introduction: Little research has examined postrehabilitation functional outcomes of periprosthetic hip fractures. Predicted functional deficits and acceptable rehabilitation outcomes for these patients are not established. This study aimed to compare functional outcomes of periprosthetic fractures to matched patients with total hip arthroplasty (THA). Materials and Methods: Cases with periprosthetic fracture (PPF) were matched for age, gender, and surgeon to primary THA cases. Only patients who had completed at least 1 year of rehabilitation were included. Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores were calculated for all surviving cases with PPF and primary THA. Secondary outcomes included length of stay and mortality. Statistical analysis was performed using Microsoft Excel and the 2-tailed Wilcoxon signed rank test. A P value of <.05 was accepted as indicative of statistical significance. Results: We identified 25 patients with PPF. Three patients were unsuitable for functional assessment. Of the cases with PPF suitable for functional assessment, 14 (14/22) were male. The median age of the PPF and the THA groups was 71 years and 68 years respectively. The median WOMAC score for the PPF group was 26 (interquartile range [IQR] 5.5-49.5) compared to that of the primary THA group, 3 (IQR 2.0-24.5; P < .05). In the PPF group, there were 7 deaths and 3 of the surviving patients had significant complications. The median length of stay in the PPF group was 13 days (IQR 10.5-35) compared to the matched group of 5 days (IQR 5-8.5; P < .05). Conclusion: Patients with PPF have markedly poorer functional outcomes than age-, gender-, and surgeon-matched patients with THA as well as prolonged length of stay. Future research should target the identification of factors that may improve functional outcomes in this growing cohort.